Assessing the real-world safety of docetaxel for non-small cell lung cancer: Insights from a comprehensive analysis of FAERS data - Lei Wang; Hui Zhao; Kunpeng Yang; Zhe Wang; Chenglun Cai; Peiyun Lv; Bao Wang (PLoS ONE, 2025)
Background Docetaxel is a key therapeutic agent in the treatment of non-small cell lung cancer (NSCLC), but comprehensive real-world data on its adverse effects remain scarce. This study aims to evaluate docetaxel-related adverse drug events by analyzing the Adverse Event Reporting System (FAERS) database of the U.S. Food and Drug Administration (FDA) from 2004 to 2024. Methods This study utilized descriptive analysis along with four heterogeneity analysis methods: Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Multivariate Gamma-Poisson Shrinker (MGPS), and Bayesian Confidence Propagation Neural Network (BCPNN), to systematically analyze 1,535 adverse event reports. Results The results identified potential adverse reactions associated with docetaxel that were not included in the drug label, such as dehydration, leukopenia, acute kidney injury, and hemoptysis, in addition to well-established adverse effects. Subgroup analysis revealed that male patients were more likely to experience respiratory-related adverse events, while female patients had a higher incidence of endocrine, metabolic, and skin-related adverse events. Patients aged over 65 years exhibited an elevated risk of cardiovascular and respiratory complications. Conclusion These findings offer critical evidence for the individualized monitoring and risk management of docetaxel in clinical practice, providing healthcare professionals with the necessary information to optimize treatment regimens and ensure the safe use of docetaxel.